DATA-DRIVEN CUSTOMIZATION: EXPLORING ADVANCED PERSONALIZED MARKETING TECHNIQUES IN THE DIGITAL AGE - Liwei, Chen; Santos, Maria Cristina (Ayden Journal of Management and Social Sciences, 2024)
The advent of the digital era has ushered in a transformative wave of big data technology, revolutionizing operations across various sectors, with a profound impact on the business landscape. In particular, big data technology has reshaped the operational logic of enterprises and transformed the dynamics of market competition. Personalized product marketing, a pivotal component of modern marketing strategy, revolves around the precise identification and fulfillment of unique consumer needs to optimize marketing effectiveness and enhance user satisfaction. However, achieving this objective hinge on the in-depth mining and accurate analysis of consumer characteristics. This paper delves into the pivotal role of big data technology in driving innovation in personalized product marketing. By providing unprecedented access to vast consumer datasets, big data technology empowers companies to glean valuable insights and conduct granular analysis of consumer behavior and preferences. Leveraging advanced analytics techniques, businesses can uncover actionable intelligence and tailor marketing strategies to individual consumer profiles, thereby enhancing engagement and fostering brand loyalty. Drawing upon insights from contemporary literature and empirical studies, this paper elucidates the transformative potential of big data technology in personalized product marketing. It explores key strategies and methodologies for leveraging big data analytics to deliver targeted and relevant marketing messages, personalized recommendations, and customized product offerings. Furthermore, the paper examines the implications of big data technology for consumer privacy, ethical considerations, and regulatory compliance. By embracing big data technology responsibly, businesses can unlock new opportunities for innovation, differentiation, and competitive advantage in the dynamic marketplace.